Comparative Effectiveness of Anticholinergic Therapy for Overactive Bladder in Women: A Systematic Review and Meta-analysis. Issue 6 (June 2015) - Reynolds, W. Stuart; McPheeters, Melissa; Blume, Jeffery; Surawicz, Tanya; Worley, Katherine; Wang, Li; Hartmann, Katherine
Abstract : OBJECTIVE: To summarize evidence about reduction in voiding and resolution of urine loss in overactive bladder comparing data from the active drug arms with the placebo arms of randomized trials. DATA SOURCES: We searched MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature, andClinicalTrials.gov in March 2014. METHODS OF STUDY SELECTION: Multiple reviewers screened original research published in English on community-dwelling women with nonneurogenic overactive bladder undergoing pharmacotherapy with medications available in the United States. Studies in which women comprised less than 75% of the population or those with a sample size less than 50 were excluded. Study designs included randomized controlled trials for meta-analysis and cohorts, case–control, and case series for harms data. Our search identified 50 randomized controlled trials from among 144 candidate publications (one was of good quality, 38 fair, and 11 poor). TABULATION, INTEGRATION, AND RESULTS: Multiple team members performed data extraction independently with secondary review of data entry to ensure quality and validity. Studies were assessed for risk of bias. Meta-analysis was performed using fixed-effects regression models. The primary outcomes and measurements were the numbers of daily voids and urge incontinence episodes. Medications delivered as a daily dose reduced urge incontinence by 1.73 episodes per day (95% confidence interval [CI] 1.37–2.09) and voids by 2.06 per day (95% CI 1.66–2.46) from 2.79 (95% CI 0.70–4.88) and 11.28 (95% CI 7.77–14.80) at baseline, respectively. Placebo reduced urge incontinence episodes by 1.06 (95% CI 0.7–1.42) and voids by 1.2 (95% CI 0.72–1.67) per day. No individual agent demonstrated superiority over another. The majority (98%) of studies reporting funding were sponsored by industry. CONCLUSION: Evidence from more than 27, 000 women participating in randomized controlled trials suggests that improvement in symptoms with anticholinergic management of overactive bladder is modest and rarely fully resolves symptoms. Abstract : Comparative evidence suggests that symptom improvement associated with anticholinergic therapy of overactive bladder is modest and rarely resolves symptoms.Supplemental Digital Content is Available in the Text.